2017
DOI: 10.1111/jcmm.13194
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin reduces Staphylococcus aureus lipoteichoic acid‐induced injury by attenuating reactive oxygen species generation and TLR2‐NFκB signalling

Abstract: Staphylococcus aureus (S. aureus) causes severe inflammation in various infectious diseases, leading to high mortality. The clinical application of antibiotics has gained a significant curative effect. However, it has led to the emergence of various resistant bacteria. Therefore, in this study, we investigated the protective effect of polydatin (PD), a traditional Chinese medicine extract, on S. aureus lipoteichoic acid (LTA)‐induced injury in vitro and in vivo. First, a significant improvement in the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 62 publications
6
49
0
Order By: Relevance
“…Specially, the level of pro-inammatory factor (TNF-a) was strongly reduced by PD, this was in accordance with many other reports. 10,33,34 Besides, the adding of TNF-a counteracted PD-induced NLRP3 inammasome inactivation via enhancing NF-kB pathway. 35 These researches hent that PD may interact with TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Specially, the level of pro-inammatory factor (TNF-a) was strongly reduced by PD, this was in accordance with many other reports. 10,33,34 Besides, the adding of TNF-a counteracted PD-induced NLRP3 inammasome inactivation via enhancing NF-kB pathway. 35 These researches hent that PD may interact with TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that SSE suppressed p65 phosphorylation, transcriptional activity, and the expression levels of target genes, such as Bax, Bcl-2, cIAP, and XIAP. It is worth noting that there are various factors that regulate the NF-κB signaling pathway, which is a double-edged sword (Chao, Deng, Li, Liang, & Huang, 2017;Jiang et al, 2011;Zhao et al, 2017). Some studies have been shown that activation of the NF-κB signaling pathway also promotes apoptosis (Chao et al, 2017;Jiang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, 2-DG monotherapy has yielded few positive results in mouse xenografts and human patients, most likely due to dose-limiting side effects or the activation pro-survival pathways in cancer cells. 17 Previous studies demonstrated that PD has antioxidant, anti-inflammatory and anti-cancer activities and it is mainly used in cardiovascular, inflammatory, neurodegenerative, metabolic and age-related diseases. Polydatin (PD, 3,4'-5-trihydroxystilbene-3-β-D-glucopyranoside, shown in Figure 1A), is extracted from the roots of Polygonum cuspidatum Sieb and can be detected in grape, peanut, hop cones, red wines, hop pellets, cocoa-containing products, chocolate products and many daily diets, is widely applied in traditional Chinese therapy.…”
mentioning
confidence: 99%
“…Polydatin (PD, 3,4'-5-trihydroxystilbene-3-β-D-glucopyranoside, shown in Figure 1A), is extracted from the roots of Polygonum cuspidatum Sieb and can be detected in grape, peanut, hop cones, red wines, hop pellets, cocoa-containing products, chocolate products and many daily diets, is widely applied in traditional Chinese therapy. 17 Previous studies demonstrated that PD has antioxidant, anti-inflammatory and anti-cancer activities and it is mainly used in cardiovascular, inflammatory, neurodegenerative, metabolic and age-related diseases. 18,19 PD exerts its anti-cancer effect in a variety of ways, such as the regulation of reactive oxygen species (ROS) 20 and inhibition of the PI3K/AKT pathway.…”
mentioning
confidence: 99%